International Criminal Police Organisation and the Challenges in the Fight against Cybercrime in Nigeria - Aminu, Audu Momoh (Kashere Journal of Politics and International Relations, 2024)
The study seeks to ascertain the challenges that have bedeviled Interpol in the fight against cybercrime in Nigeria. On the second assumption of the space transition theory of Jaishankar (2008) which believes that Identity Flexibility, dissociative anonymity and poor deterrence factors that characterized the cyberspace is a motivator of cybercrime, the study adopted a descriptive pattern and mixed method to collect data from three hundred and seventy-five (375) respondents randomly and purposively selected from Interpol National Central Bureau (NCB) Abuja, Nigeria Police Force (NPF), Economic and Financial Crime Commission (EFCC) and the Department of State Services (DSS). The study found that inadequate finance, cyber-anonymity and poor deterrence are the most serious challenges that have bedeviled Interpol in the fight against Cybercrime in Nigeria. It therefore recommends that Interpol member countries, partners and stakeholders need to fulfill their financial obligations in line with the Interpol Constitution to enable it carry out laudable programs and activities and to effectively fight the menace of Cybercrime in Nigeria. That, all law enforcement agencies involved in the fight against Cybercrime in Nigeria must step up their synergy, Intelligence Sharing and Utilization of the Interpol platforms/tools in order to effectively deal with the level of cyber-anonymity and poor deterrence that has pervaded the fight against cybercrime in Nigeria and for effective result.